Entropy of Mixing of Cadmium-based Liquid Alloys - Chakrabarti, S. K.; Jha, B. K.; Jha, I. S. (Journal of Nepal Chemical Society, 2010)
Cadmium is a highly reactive metal. At the time of formation of binary alloys in liquidphase it often forms complexes. In the present work we have considered two such complexforming binary liquid alloys of cadmium e.g. Cd-Na and Cd-Mg. The former alloy showsanomaly in its thermodynamic properties of mixing. On the other hand, the alloyingbehavior of the latter one is symmetric around the equi-atomic composition. We havecomputed their entropy of mixing (SM) for different concentrations of the ingredients byusing the quasi-lattice chemical model. The results explain the observed anomaly as well assymmetry in SM of the present alloys.Keywords: Binary liquid alloys of cadmium; Quasi-lattice chemical model; Entropy of mixingDOI: 10.3126/jncs.v26i0.3629Journal of Nepal Chemical SocietyVol. 26, 2010Page:40-45